Penguatan Ekonomi Berkelanjutan Berbasis Manajemen Administrasi Usaha Budidaya Ikan Nila: Strengthening a Sustainable Economy Based on Administrative Management of Tilapia Cultivation Businesses - Rekarti, Endi; Mubarok, Faizul; Wibowo, Martino; Sultan, Zulkifli; Widokarti, Joko Rizkie (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Tilapia is a popular type of fish in the global aquaculture industry, with the advantage of genetically enhanced strains for fast growth and feed efficiency. However, cultivators often need help with administrative management, suboptimal productivity, and limited knowledge about the latest cultivation technology. The community service program, which involves the Berkah Jaya tilapia cultivator group in Pandeglang, aims to increase understanding and overcome these challenges through assistance focusing on locally based solutions. Strategies include disease control, water quality management, and infrastructure improvements. Adopting appropriate technology and improving group administrative management are the main strategies for achieving sustainability and increasing productivity in tilapia farming.